THE CAPITAL STRUCTURE OF LISTED FIRMS AND DECLINING MARKET CONDITIONS - Schollenberger, Hans J. (My University, 2011)
The objective of this study was to determine the effects of a declining market trend or bear period on the capital structure of companies listed on the JSE between 1999 and 2003. A significant finding using nonparametric statistical analysis, was that the sector debt-equity ratios had remained unchanged over the bear period. However, once companies were divided into categories defined by return on investment (ROI), cost of debt, price-to-book ratio and the net operating profit after tax (NOPAT), some changes in capital structure were apparent. Firstly, for companies with an ROI greater than the cost of debt and a price-to-book ratio greater than the median it was found that the overall debt to equity ratios of these firms had remained unchanged. However, as the definition of debt included both interest and non-interest bearing liabilities, the increased use of debt as a proportion of total liabilities was confirmed through additional hypothesis testing. This suggested that companies with a price-to-book ratio greater than the median derived increased benefit from the tax shield and engaged in value maximising behaviour. Companies that had an ROI greater than the cost of debt and a price-to-book ratio less than the median maintained their debt-equity ratios and did not increase the proportion of interest- bearing to total liabilities. Companies with a cost of debt less than the return on investment, implying reduced profitability, were classified further into those with a positive and a negative NOPAT. For firms with a positive NOPAT it was found that these firms resorted to increased debt funding and the greater use of short term liabilities in particular. This finding was regarded as consistent with the behaviour of less profitable firms that tended to resort to increased levels of debt financing to maintain III financial flexibility, although this finding may have been independent of the economic cycle. Lastly, companies with a cost of debt less than ROI and a negative NOPAT were found to have significantly increased their debt-equity ratios as compared to before the bear period. As the levels of debt remained unchanged, however, the increased debt-equity ratios were shown to be a direct result of cumulative retained losses, which had eroded shareholders’ equity. Overall, the findings did not support the active management of capital structure, which would have entailed the retiring of debt during bear periods yielding a decrease in debt-equity ratios. The results did seem to show evidence of consistent financial policy, particularly for companies with a return on investment greater than the cost of debt
MBA thesis - WBS
Keywords: Capital structure of companies; Economic conditions